Design and Testing of Synthetic Catalytic Amyloids Based on the Active Site of Enzymes - Castillo-Nara, A; Diaz-Espinoza, R (Humana Press Inc., 2022)
The amyloid fold is nowadays recognized as an alternative conformation accessible to different proteins and peptides. The highly stable and ordered structural organization of amyloid fibrils can be exploited for the design of novel nanomaterials with emergent properties. Recent works have demonstrated that the functional features of the active site of enzymes can be partially recreated using this fold as a scaffold to develop catalytically active amyloids. We describe in this chapter a protocol to design functionally active amyloids that emerge from the self-assembly in vitro of synthetic peptides with sequences based on the active site of enzymes. Using this protocol, we show the development of amyloids that catalyze the metal-dependent hydrolysis of the phosphoanhydride bonds of nucleoside triphosphates. © 2022, The Author(s), under exclusive license to Springer Science+Business Media, LLC, part of Springer Nature.